Eksistensi dan Karya Kristus menurut Surat Filipi 2:5-11 dan Relevansinya bagi Gereja Masa Kini - Tabita Kustiati; Paulus Kunto Baskoro (Sekolah Tinggi Alkitab Jember, 2023)
There are several views on the existence of Christ among various groups and teachings in the world. The Holy Bible as the main guide for Christians states that Christ is God who took human form and died on the cross as the atonement for the sins of mankind. However, other religions as well as other beliefs such as some of the classical teachings of Judaism, Islam, or Jehovah's Witnesses do not recognize Christ as God. There are also some groups who think Christ was just an ordinary man. The real existence and work of Christ is God who was incarnated as a human in the flesh, humbled himself and died on the cross to atone for human sins, and rose on the third day. In the present, the existence and work of Christ can be illustrated by the example of true believers and the fellowship of believers. This paper was conducted using a literature study approach to evaluate the relevance of the chapter for the church today, showing how this view of the existence of Christ can be used to strengthen faith, increase obedience, and help the church spread the gospel. Through this paper, we will also examine how Christ's work can become a basic guideline and motivation to live according to Christ's will.Pandangan terhadap eksistensi Kristus bervariasi di antara berbagai kelompok dan ajaran di dunia. Kitab Suci Alkitab sebagai panduan utama orang Kristen menyatakan bahwa Kristus adalah Tuhan yang mengambil rupa manusia dan mati di kayu salib sebagai penebus dosa umat manusia. Namun, agama-agama lain serta kepercayaan lain seperti beberapa ajaran klasik Yahudi, Islam, atau Saksi-saksi Yehuwa tidak mengakui Kristus sebagai Tuhan. Ada juga beberapa kelompok yang menganggap Kristus hanyalah seorang manusia biasa. Eksistensi dan karya Kristus yang sesungguhnya adalah Allah yang telah berinkarnasi menjadi manusia di dalam daging, dan telah merendahkan dirinya dan mati di kayu salib untuk menebus dosa manusia dan bangkit di hari yang ketiga. Dalam masa kini, eksistensi dan karya Kristus dapat digambarkan dengan teladan orang percaya dan persekutuan orang percaya yang benar. Tulisan ini dilakukan dengan pendekatan studi pustaka untuk mengevaluasi relevansi pasal bagi gereja masa kini , menunjukkan bagaimana pandangan tentang eksistensi Kristus ini dapat digunakan untuk memperkuat iman, meningkatkan ketataatan, dan membantu gereja dalam penyebaran injil. Melalui tulisan ini juga akan dikaji bagaimana karya kristus dapat menjadi pedoman dasar dan motivasi untuk hidup sesuai dengan kehendak Kristus.